METODE MOORA DENGAN PERFORMA KLUB LIGA INGGRIS TERHADAP KLASEMEN AKHIR - Muhammad Jauhar Fardani; Arya Anggara; Agusta Praba Ristadi Pinem (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
The English Premier League (EPL) is a highly popular football league with intense competition among clubs every season. To assess the performance of EPL clubs objectively, data-driven evaluation is required to measure various aspects of team performance. This study aims to evaluate the performance of EPL clubs in the 2018/2019 season using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method. MOORA was chosen because it can consider quantitative criteria such as goals scored, goals conceded, clean sheets, shots on target, total corner kicks, average ball possession, number of cards, and fouls. The data used includes statistics from 20 EPL clubs. The results show that top-ranked clubs like Manchester City, Liverpool, and Chelsea had consistent results with their final positions in the standings. However, differences were found in some clubs, such as Wolverhampton, which finished 7th in the final standings but ranked 10th according to MOORA. The analysis reveals that the MOORA ranking results, based on non-point statistical criteria, have a very high correlation with the final standings, with a Spearman correlation value of 0.9624. These findings emphasize the relevance of non-point statistical data in evaluating club performance quantitatively. This study contributes to the development of data-driven evaluation methodologies for football, providing valuable insights for club managers and sports analysts in identifying team strengths and weaknesses objectively, thereby supporting more accurate decision-making in strategic planning.